The use of an automatic remote weight management system to track treatment response, identified drugs supply shortage and its consequences: A pilot study - Idan Roth; Ohad Cohen (Digital Health)
Objective The objective of this pilot study is to evaluate the feasibility of using an automatic weight management system to follow patients’ response to weight reduction medications and to identify early deviations from weight trajectories. Methods The pilot study involved 11 participants using Semaglutide for weight management, monitored over a 12-month period. A cloud-based, Wi-Fi-enabled remote weight management system collected and analyzed daily weight data from smart scales. The system's performance was evaluated during a period marked by a Semaglutide supply shortage. Results Participants achieved a cumulative weight loss of 85 kg until a supply shortage-induced trough in October 2022. This was followed by a 6–8 week plateau and a subsequent 13 kg cumulative weight gain. The study demonstrated the feasibility of digitally monitoring weight without attrition over 12 months and highlighted the impact of anti-obesity drug (AOD) supply constraints on weight trajectories. Conclusions The remote weight management system proved important for improving clinic efficacy and identifying trends impacting obesity outcomes through electronic data monitoring. The system's potential in increasing medication compliance and enhancing overall clinical outcomes warrants further research, particularly in light of the challenges posed by AOD supply fluctuations.